Corpora in Language Research in Malaysia - Hajar Abdul Rahim (Kajian Malaysia, 2014)
Since the creation of the first generation of computer-readable corpora, pioneered by the Brown Corpus in the 1970s, corpora have been extensively used in virtually all branches of linguistics. This article discusses corpus-based research and its development in the Malaysian linguistic scenario over the last three decades in considering its status and prospect as a research method. The discussion shows that research in Malay and English in the country has benefited from the use of corpora. In the last decade especially, there has been a surge of interest in corpora as a research tool in Malay and English, evidenced by the rise in research and publications on Malay linguistic description, English learner language, and Malaysian English as a local variety. Despite the encouraging development, there is still much to be gained from the use of corpora and corpus analysis in the linguistic description of Malay dialects, variation and pedagogy, English language pedagogy, Malaysian English and other language varieties including endangered and indigenous languages in the country